A Clinical Perspective on Musculoskeletal Infection Treatment Strategies and Challenges. (April 2015) - Shirwaiker, Rohan A.; Springer, Bryan D.; Spangehl, Mark J.; Garrigues, Grant E.; Lowenberg, David W.; Garras, David N.; Yoo, Jung U.; Pottinger, Paul S.
Abstract : Orthopaedic implants improve the quality of life of patients, but the risk of postoperative surgical site infection poses formidable challenges for clinicians. Future directions need to focus on prevention and treatment of infections associated with common arthroplasty procedures, such as the hip, knee, and shoulder, and nonarthroplasty procedures, including trauma, foot and ankle, and spine. Novel prevention methods, such as nanotechnology and the introduction of antibiotic-coated implants, may aid in the prevention and early treatment of periprosthetic joint infections with goals of improved eradication rates and maintaining patient mobility and satisfaction.